Preparation of Layer-by-Layer Films Composed of Polysaccharides and Poly(Amidoamine) Dendrimer Bearing Phenylboronic Acid and Their pH- and Sugar-Dependent Stability - Yoshida, Kentaro (Materials (Basel), 2016)
Layer-by-layer films composed of polysaccharides and poly(amidoamine) dendrimer bearing phenylboronic acid (PBA-PAMAM) were prepared to study the deposition behavior of the films and their stability in buffer solutions and in sugar solutions. Alginic acid (AGA) and carboxymethylcellulose (CMC) were employed as counter-polymers in constructing LbL films. AGA/PBA-PAMAM films were successfully prepared at pH 6.0–9.0, whereas the preparation of CMC/PBA-PAMAM film was unsuccessful at pH 8.0 and 9.0. The results show that the LbL films formed mainly through electrostatic affinity between PBA-PAMAM and polysaccharides, while, for AGA/PBA-PAMAM films, the participation of boronate ester bonds in the films was suggested. AGA/PBA-PAMAM films were stable in the solutions of pH 6.0–9.0. In contrast, CMC/PBA-PAMAM films decomposed at pH 7.5–9.0. The AGA/PBA-PAMAM films decomposed in response to 5–30 mM fructose at pH 7.5, while the films were stable in glucose solutions. Thus, AGA is useful as a counter-polymer for constructing PBA-PAMAM films that are stable at physiological pH and decompose in response to fructose.